Monotonic and cyclic axial compressive responses of concrete specimens externally confined with different types of FRP composites: experimental and analytical investigations - Rodsin, Kittipoom; Hussain, Qudeer; Parichatprecha, Rattapoohm (My University, 2023)
The main objective of this study was to investigate the monotonic and cyclic axial stress versus strain response of the concrete confined with different types of fiber reinforced polymer (FRP) composites such as cotton fiber rope reinforced polymer (CFRRP), glass fiber reinforced polymer (GFRP) composites and carbon fiber reinforced polymer (CFRP) composites. Another objective was to investigate the applicability of existing ultimate strength models to predict the ultimate strength of concrete confined with CFRRP, GFRP and CFRP composites. For this, a total number of 28 concrete cylinders were cast, strengthened and tested under pure axial compression. The concrete cylinders were strengthened with two and four layers of FRPs. The experimental results indicate that all kinds of FRPs are very useful to alter the ultimate strength and strain of the confined concrete. The highest increase in ultimate strength was recorded for CFRP composite confined specimens and the highest increase in ultimate strain was observed for CFRRP composite confined specimens. Further, both ultimate strength and ultimate strains are found higher in the case of cyclic loads compared with the monotonic load. In general, the stress versus strain curves of cotton fiber rope and glass FRPs are found trilinear. Whereas, stress versus strain curves of CFRP confined specimens are observed to be bilinear. Existing ultimate strength models developed for CFRRP and CFRP composites are found well accurate to predict the ultimate strengths of CFRRP and CFRP confined concrete specimens tested in this study.
Keywords: analytical models; axial compression; carbon; cotton; cyclic load; fiber reinforced polymer composites